SP17 How to make your thoracic epidural work?. (11th August 2022) - Coppens, Steve; Raudsepp, Mark; Hoogma, Danny Feike; Dreelinck, Rebekka; Loon, Phillipe Van
Abstract : Introduction: Although High Thoracic Epidural analgesia (HTEA) has been replaced as a gold standard in minimal invasive surgical procedures, it still is a viable technique in open major surgery (e.g., vascular, thoracic, abdominal). 1 Performing a HTEA is difficult to master. 2 Published failure rates average from moderate to high. 3, 4 Reduced caseloads further diminish training and competence proficiency, augmenting the problem. 5 We will examine common pitfalls and barriers, while determining factors for success. Finally evaluate novelties to improve favorable results and investigate all modalities to aid successful placement. Discussion: Enhanced Recovery programs and minimal invasive surgical techniques have had a detrimental impact on the choice for thoracic epidural as regional analgesic technique. Multimodal analgesic strategies, including fascial plane blocks, are indeed a key element in modern day low impact surgery. 6 However, postoperative pain management for major surgery like esophagectomies, thoracotomies, open abdominal aortic surgery and any major open hepatobiliary surgery remain a challenge for anesthesiologists. Even if the effect on morbidity and mortality is controversial, HTEA still has major benefit in reducing opioid consumption combined with a well-known effect on surgical inflammatory cascade. 7 Aiding Success. First of all, to adapt to diminishing caseloads it is imperative that modern teaching methods are implemented. Simulators, online tools, webinars, video tutorials can have a tremendous impact on training. A basic (lumbar) epidural simulator is a small investment for any anesthetic department to make, with a great return on investment. 8 Video-based learning systems have shown to provide some gains. 2 While online tools like Virtual Spine: lumbar anatomy, 3D model, vertebra, spinal cord, dura, meninges, cauda equina, ultrasound (utoronto.ca) have a profound influence on our anatomical knowledge, unfortunately there is currently not enough evidence on beneficial impact on performance. Secondly ultrasound (US), although not mandatory to perform thoracic epidurals, can make life easier and also increase enthusiasm of young colleagues for the technique. US has not proven to increase success rates yet, however it facilitates identifying midline and familiarize the unfamiliar with the anatomy. 9 Thirdly the thoracic epidural should be taught properly with respect to all small clinical pearls. Positioning, preparation, adequate communication, effective local anesthesia, organization and adaptation are extremely important and will probably be the best advice to improve your prowess. A locoregional fellowship where a sufficient number of thoracic epidurals are still placed is your best bet when fishing for these pearls. 10 Lastly the loss of resistance technique is a subtle art indeed. Even with excellent coaching and teaching, this skill cannot be easily transferred to the onlooker. To help ascertain a correct loss of resistance technique there are some tips and tricks up our sleeves. The hanging drop approach can help needle advancement meticulously and carefully, while using both hands. Various spring-loaded syringes have also been developed to aid the developing skills. Results with these devices have been mostly mixed. 11 Ascertaining success. As described above, assistance of clinical pearls in ascertaining the accurate placement of an epidural needle and catheter play a crucial role. Generally, you can scrutinize three different clinical questions. Was the loss clear? Was the threading of the catheter easy (or even possible) and did patients feel a slight paresthesia while threading the catheter? And finally, is saline column in the epidural catheter dropping steadily when elevated? There are several more robust ways to confirm success. Fluoroscopy has already shown to be one of the best predictors of exact epidural catheter placement. It also has the added advantage of lowering failure rate and almost eliminating dislodgements completely. However, the investment in equipment, training, radiological protection and interpretation of imaging has hindered any broad implementation. Waveform analysis 12 can either be used with an auditive sound adapter, which requires a specific device. 12 In addition, it can be used by placing a pressure transducer on the epidural needle and examining the presence of a pulsatile pressure wave. Tsui test 13 or epidural electrical stimulation test (EST) is in my humble opinion the best way to detect perfect positioning of the catheter. 13 However, it is very underutilized, probably due to poor understanding and lack of availability of a 'Johans Adapter' ( figure 1 ). Other devices and future developments like bioimpedance or optical reflectance spectroscopy may still impact the way we place thoracic epidurals, however fall beyond the scope of this lecture. Conclusion: HTEA is a very effective anesthetic technique which should be reserved for major surgery and preserved for future generations. The training of this approach is progressively more difficult with ever decreasing numbers. Online resources, ultrasound and simulators should be implemented to reach proficiency. Clinical pearls, optimal caseload and training by experts is the best way to go. More research is needed in tools like special syringes and waveform analysis devices to analyze their usefulness. The Tsui test is the ultimate practical test to evaluate successful catheter placement. References: Bachman SA, Lundberg J, Herrick M. Avoid suboptimal perioperative analgesia during major surgery by enhancing thoracic epidural catheter placement and hemodynamic performance. Regional Anesthesia & Pain Medicine 2021; 46: 532–534. Seering M, Campos JH. Educational Methods to Improve Thoracic Epidural Block Proficiency for Residents: Video-Based Education Versus Bedside Education. Journal of Cardiothoracic and Vascular Anesthesia 2020; 34 : 3049–3051. Hermanides J, Hollmann MW, Stevens MF, Lirk P. Failed epidural: Causes and management. British Journal of Anaesthesia 2012; 109 : 144–154. Elsharkawy H, Sonny A, Chin K. Localization of epidural space: A review of available technologies. Journal of Anaesthesiology Clinical Pharmacology 2017; 33 : 16. Tran DQH, van Zundert TCRV, Aliste J, Engsusophon P, Finlayson RJ. Primary failure of thoracic epidural analgesia in training centers: The invisible elephant? Regional Anesthesia and Pain Medicine 2016; 41 : 309–313. Sondekoppam R v., Tsui BCH. 'Minimally invasive' regional anesthesia and the expanding use of interfascial plane blocks: the need for more systematic evaluation. Canadian Journal of Anesthesia/Journal canadien d'anesthésie 2019; 66 : 855–863. Pöpping DM, Elia N, van Aken HK, Marret E, Schug SA, Kranke P et al. Impact of Epidural Analgesia on Mortality and Morbidity After Surgery. Annals of Surgery 2014; 259 : 1056–1067. Vaughan N, Dubey VN, Wee MYK, Isaacs R. A review of epidural simulators: Where are we today? Medical Engineering & Physics 2013; 35 : 1235–1250. Auyong DB, Hostetter L, Yuan SC, Slee AE, Hanson NA. Evaluation of Ultrasound-Assisted Thoracic Epidural Placement in Patients Undergoing Upper Abdominal and Thoracic Surgery. Regional Anesthesia and Pain Medicine 2017; 42 : 204–209. Lorin MI, Palazzi DL, Turner TL, Ward MA. What is a clinical pearl and what is its role in medical education? Medical Teacher 2008; 30 : 870–874. Riley ET, Carvalho B. The Episure TM Syringe: A Novel Loss of Resistance Syringe for Locating the Epidural Space. Anesthesia & Analgesia 2007; 105 : 1164–1166. McKendry RA, Muchatuta NA. Pressure waveforms to assess epidural placement: is there a role on delivery suite? Anaesthesia 2017; 72 : 815–820. Kwofie MK, Launcelott G, Tsui BCH. Determination of thoracic epidural catheter placement: electrical epidural stimulation (Tsui test) is simple, effective, and under-utilized. Canadian Journal of Anesthesia/Journal canadien d'anesthésie 2019; 66 : 360–364.